A novel multi-modal platform to image molecular and elemental alterations in ischemic stroke - Caine, S.; Hackett, Mark; Hou, H.; Kumar, S.; Maley, J.; Ivanishvili, Z.; Suen, B.; Szmigielski, A.; Jiang, Z.; Sylvain, N.; Nichol, H.; Kelly, M. (Academic Press, 2016)
© 2016 Elsevier Inc.Stroke is a major global health problem, with the prevalence and economic burden predicted to increase due to aging populations in western society. Following stroke, numerous biochemical alterations occur and damage can spread to nearby tissue. This zone of “at risk” tissue is termed the peri-infarct zone (PIZ). As the PIZ contains tissue not initially damaged by the stroke, it is considered by many as salvageable tissue. For this reason, much research effort has been undertaken to improve the identification of the PIZ and to elucidate the biochemical mechanisms that drive tissue damage in the PIZ in the hope of identify new therapeutic targets. Despite this effort, few therapies have evolved, attributed in part, to an incomplete understanding of the biochemical mechanisms driving tissue damage in the PIZ. Magnetic resonance imaging (MRI) has long been the gold standard to study alterations in gross brain structure, and is frequently used to study the PIZ following stroke. Unfortunately, MRI does not have sufficient spatial resolution to study individual cells within the brain, and reveals little information on the biochemical mechanisms driving tissue damage. MRI results may be complemented with histology or immuno-histochemistry to provide information at the cellular or sub-cellular level, but are limited to studying biochemical markers that can be successfully “tagged” with a stain or antigen. However, many important biochemical markers cannot be studied with traditional MRI or histology/histochemical methods. Therefore, we have developed and applied a multi-modal imaging platform to reveal elemental and molecular alterations that could not previously be imaged by other traditional methods. Our imaging platform incorporates a suite of spectroscopic imaging techniques; Fourier transform infrared imaging, Raman spectroscopic imaging, Coherent anti-stoke Raman spectroscopic imaging and X-ray fluorescence imaging. This approach does not preclude the use of traditional imaging techniques, and rather it should be use to complement traditional methods such as MRI or histology and immunohistochemistry, to gain a greater insight into disease mechanisms. We demonstrate the potential of this approach by characterizing biochemical alterations within the PIZ 24 h after the induction of photothrombotic stroke in mice. Substantial molecular and elemental alterations were identified in the PIZ 24 h after stroke that are consistent with tissue swelling and edema, but not oxidative stress. This reveals important mechanistic information, that could not previously be obtained, which should be considered in future studies aimed at developing therapeutic intervention from this model.